The rationalization of production of magnesium alloy drop forgings using FEM simulation regarding forging process - Mária Kapustová (Tehnički Vjesnik, 2017)
In this paper a method of precision die forging without flash of magnesium alloy AZ31 is described. This method brings material and energy savings compared to common method of forging with flash. Computer simulation of technological process of forging has an important role for development of progressive methods of precision die forging. The forging of Mg alloy in closed die described in this paper was verified using program MSC.SuperForge. Experiment of forging without flash of lever-shaped forged piece from magnesium alloy AZ31 was successfully performed at laboratory conditions. Final drop forging has no folds or other defects on its surface, which is confirmed by correct selection of forging temperature 400 °C and semi-product shape. Achieved results of the experiment will be important for working team of technologists at introducing forging without flash regarding non-ferrous drop forgings to production practice.